Riemann Zeta function

Calculus Level 4

Compute the value of k = 1 ( 1 + 1 p k 2 + 1 p k 4 ) \prod_{k=1}^\infty \left(1+\frac{1}{p_{k}^2}+\frac{1}{p_{k}^4}\right) where p k p_k is the k k th prime.


The answer is 1.6168922051.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

ChengYiin Ong
Jun 10, 2020

We have k = 1 ( 1 + 1 p k 2 + 1 p k 4 ) = k = 1 ( p k 4 + p k 2 + 1 p k 4 ) = k = 1 ( p k 4 + 2 p k 2 + 1 p k 2 p k 4 ) = k = 1 ( p k 2 p k + 1 ) ( p k 2 + p k + 1 ) p k 4 = k = 1 ( p k + 1 ) ( p k 2 p k + 1 ) ( p k 1 ) ( p k 2 + p k + 1 ) p k 4 ( p k + 1 ) ( p k 1 ) = k = 1 p k 6 1 p k 6 p k 4 = k = 1 1 1 p k 6 1 1 p k 2 = k = 1 ( 1 1 p k 2 ) 1 ( 1 1 p k 6 ) 1 = ζ ( 2 ) ζ ( 6 ) = 315 2 π 4 \displaystyle\prod_{k=1}^\infty (1+\frac{1}{p_{k}^2}+\frac{1}{p_{k}^4})=\displaystyle\prod_{k=1}^\infty (\frac{p_{k}^4+p_{k}^2+1}{p_{k}^4})=\displaystyle\prod_{k=1}^\infty (\frac{p_{k}^4+2p_{k}^2+1-p_{k}^2}{p_{k}^4})=\displaystyle\prod_{k=1}^\infty \frac{(p_{k}^2-p_{k}+1)(p_{k}^2+p_{k}+1)}{p_{k}^4}= \displaystyle\prod_{k=1}^\infty \frac{(p_{k}+1)(p_{k}^2-p_{k}+1)(p_{k}-1)(p_{k}^2+p_{k}+1)}{p_{k}^4(p_{k}+1)(p_{k}-1)}=\displaystyle\prod_{k=1}^\infty \frac{p_{k}^6-1}{p_{k}^6-p_{k}^4} =\displaystyle\prod_{k=1}^\infty \frac{1-\frac{1}{p_{k}^6}}{1-\frac{1}{p_{k}^2}}=\displaystyle\prod_{k=1}^\infty \frac{(1-\frac{1}{p_{k}^2})^{-1}}{(1-\frac{1}{p_{k}^6})^{-1}}=\frac{\zeta {(2)}}{\zeta {(6)}}=\frac{315}{2\pi^4}

@ChengYiin Ong , k k should start at 1 1 and not 0 0 .

Chew-Seong Cheong - 1 year ago

You're right

ChengYiin Ong - 1 year ago
Lingga Musroji
Jun 13, 2020

First:

( 1 + a 2 + a 4 ) ( 1 a 2 ) = ( 1 a 2 ) + ( a 2 a 4 ) + ( a 4 a 6 ) = 1 a 6 1 + a + a 2 = 1 a 6 1 a 2 (1+a^2+a^4)(1-a^2)=(1-a^2)+(a^2-a^4)+(a^4-a^6)=1-a^6\\1+a+a^2=\frac{1-a^6}{1-a^2}

Second:

ζ ( s ) = p p r i m e ( 1 1 p s ) \zeta(s)=\prod_{p\in prime}\left(1-\frac{1}{p^{-s}}\right)

Third:

( 1 1 p s ) 1 = 1 1 1 p s = 1 1 p s \left(1-\frac{1}{p^s}\right)^{-1}=\frac{1}{1-\frac{1}{p^s}} =\frac{1}{1-p^{-s}}

Finally:

p p r i m e ( 1 + 1 p k + 1 p k 2 ) = p p r i m e ( 1 1 p k 6 1 1 1 p k 2 ) = p p r i m e ( 1 1 p k 6 ) p p r i m e ( 1 1 p k 2 ) = p p r i m e ( 1 1 p k 2 ) 1 p p r i m e ( 1 1 p k 6 ) 1 = p p r i m e ( 1 1 p 2 ) p p r i m e ( 1 1 p 6 ) = ζ ( 2 ) ζ ( 6 ) = 315 2 π 4 \prod_{p\in prime}\left(1+\frac{1}{p_k}+\frac{1}{p_k^2}\right)=\prod_{p\in prime}\left(\frac{1-\frac{1}{p_k^6}}{1-\frac{1}{1-p_k^2}}\right) =\frac{\prod_{p\in prime}\left(1-\frac{1}{p_k^6}\right)}{\prod_{p\in prime}\left(1-\frac{1}{p_k^2}\right)} \\=\frac{\prod_{p\in prime}\left(1-\frac{1}{p_k^2}\right)^{-1}}{\prod_{p\in prime}\left(1-\frac{1}{p_k^6}\right)^{-1}} =\frac{\prod_{p\in prime}\left(\frac{1}{1-p^{-2}}\right)}{\prod_{p\in prime}\left(\frac{1}{1-p^{-6}}\right)} =\frac{\zeta(2)}{\zeta(6)}=\frac{315}{2\pi^4}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...